Croatia and Hungary in the Hungarian-Polish Chronicle - Grzesik, Ryszard (Balcanica Posnaniensia. Acta et studia, 2020)
In the Hungarian-Polish Chronicle, written at the turn of the 1230s, one can find a piece of information on Croatia. It is a note on St Paul’s mission in Split, where he allegedly was a Bishop before his travel to Rome, where he found his martyrdom and a story of a Croatian ruler, who was killed by his subjects. The first story used a motif, which was probably popular in medieval Dalmatia, that St Paul was a real apostle of that region. It was Constantin Porphyrogenitus who noted his presence in the context of Adriatic islands and Thomas, archdeacon of Split (Spalato) who argued against this idea. The another story could reflect a tradition of a death of a Great-Moravian ruler, which was mythologized and deprived of a spatial and temporal context. It is interesting that the Hungarians’ raid to their new homeland was presented else as in another sources and in the reality: not from the north-east (Ruthenian territories), but from south (Slavonia). The northern part of Slavonia was nominated Hungary according to the Chronicle, which reflected the geographical and economical unity of Hungarian medieval Kingdom.